Gross Capital Flows, Common Factors, and the Global Financial Cycle - Barrot, Luis-Diego; Serven, Luis (World Bank, Washington, DC, 2018)
This paper assesses the international comovement of gross capital inflows and outflows using a two-level factor model. Among advanced and emerging countries, capital flows exhibit strong commonality: common (global and country group-specific) factors account, on average, for close to half of their variance. There is a contrast across groups: common factors dominate advanced-country capital flows, while idiosyncratic factors dominate emerging- country flows and, especially, developing-country flows. The reason is the much larger role of global factors among advanced countries. Importantly, these findings apply to both inflows and outflows: their respective common factors are very similar -- although global factors play a bigger role for outflows than for inflows. The commonality of flows reflects a global cycle, summarized by a small set of variables (the VIX, the U.S. real interest rate and real exchange rate, U.S. GDP growth, and world commodity prices) that explain much of the variance of the estimated factors -- especially the global factors. Over time, the quantitative role of the common factors exhibits a "globalization" stage up to 2007, during which they acquire growing importance, followed by a phase of "deglobalization" post-crisis. Greater financial openness, deeper financial systems, and more rigid exchange rate regimes amplify countries' exposure to the global financial cycle.